(I can't get no) job satisfaction? Differences by sexual orientation in Sweden - Lina Aldén; Mats Hammarstedt; Hanna Swahnberg (Research Institute of Industrial Economics (IFN), 2018)
We present results from a unique nationwide survey conducted in Sweden on sexual orientation and job satisfaction. Our results show that gay men, on average, seem more satisfied with their job than heterosexual men; lesbians appear less satisfied with their job than heterosexual women. However, the issue of sexual orientation and job satisfaction is complex since gay men, despite their high degree of job satisfaction, like lesbians find their job more mentally straining than heterosexuals. We conclude that gay men and lesbians are facing other stressers at work than heterosexuals do. We also conclude that discrimination and prejudice may lead gay men to have low expectations about their job; these low expectations may translate into high job satisfaction. In contrast, prejudice and discrimination may hinder lesbians from realizing their career plans, resulting in low job satisfaction.
Keywords: J28; J15; J71; 330; Job satisfaction; Sexual orientation